Social Logic of Morphological Evolution of Temple Towns of Kerala, India :Understanding the cultural influence on the spatial configuration of Temple Towns - Josna Raphael P. and A.K.Kasthurba (International Journal of Chemical, Environmental & Biological Sciences (IJCEBS), 2015)
Built environments are basically organization of space as they consist of space (un‐ built) and matter (built). The spaces are linked to each other, forming a “system of spaces”. The way these individual spaces are formed and most importantly, linked together; is responsible for spatial configuration of the built environment. The socio cultural aspects in terms of the user preferences are responsible for the evolution of spatial configuration in a built environment, over a period of time. Thus, the built environment and the social environment are two sides of the same coin and that is the “system of spaces”. The research is intended with the need of understanding built environments in a selected traditional urban core of Kerala which is the cultural capital as well as a traditional temple town.The place is analysed in terms of their configuration to understand culture specific human preferences about space proxemics. The research has been fostered by questions: (1) How to understand and quantify the spatial configurations of organically evolved built environments of urban cores? (2) To deduce the human aspects in terms of user preferences about space proxemics The strong influence of various factors like religious, cultural, historic etc is analyzed to trace the development of architecture in Trichur. The analysis shows the integration of cultural aspects as the most important defining aspect of the spatial configuration of the traditional urban core.